Conflicting versus reinforcing private information, information aggregation, and the time series properties of asset prices - Schnitzlein, Charles; Chelley-Steeley, Patricia; Steeley, James M (Journal of Banking & Finance, 2024)
We study how the relationship between independent private information signals affects information aggregation in laboratory asset markets. We employ two mechanisms, a continuous double auction and a prediction market. Under both mechanisms, when information is reinforcing, partial information aggregation occurs. When information is in conflict, information aggregation lessens and attempts to profit from private information frequently harm informational efficiency . In both mechanisms, results become stronger with experience in previous experimental sessions, and provide a private information benchmark for studies of the implications of conflicting public information. Under reasonable assumptions, our results are consistent with both momentum effects and weak reversals.